1527 Venous thromboprophylaxis in ambulatory emergency department patients managed with lower limb immobilization. A national survey. Issue 12 (22nd November 2022) - Crainie, Chloe; Cooper, Jamie
Abstract : Aims, Objectives and Background: Approximately 2% of patients discharged from the Emergency Department (ED) in lower limb immobilisation after injury will develop symptomatic venous thromboembolism (VTE). Pharmacological thromboprophylaxis, in the form of low molecular weight heparin (LMWH) or fondaparinux can approximately halve this risk. However, it is not clear which patients would clinically benefit from this intervention, or if direct oral anticoagulants (DOACs) can be recommended for this indication. In the United Kingdom (UK), national guidance recommends patients be risk assessed to stratify thromboprophylaxis decisions. Consequently, various risk assessment methods (RAMs) have been evaluated but consensus is limited on the optimal approach. Aim: A national survey of UK practice in this clinical area to characterise variation and inform a recently commissioned research call. Method and Design: A 10-question electronic survey was created via the Smart Survey platform® and distributed to UK Type 1 EDs during February and March 2022. Duplicate ED responses were excluded and data analysed using Smart Survey Analytics. Results and Conclusion: A total of 116 (69%) of Type 1 EDs submitted a response. Nearly all (>95%) would consider thromboprophylaxis when a rigid cast was applied, but this was less for removable semi-rigid splints of the ankle (53%) or knee (20%). Of responding EDs, 83% used a RAM; most often a locally developed tool or NICE guidance. Published RAMs designed specifically for use in these patients were used by only 16% of EDs. When indicated, the majority of departments reported using LMWH (70%) in accordance with NICE guidelines, but 29% used a DOAC. Duration of thromboprophylaxis prescription also varied widely ( table 1 ). This national survey highlights considerable variation in all aspects of clinical practice regarding VTE prevention in patients managed with temporary lower limb immobilisation after injury. Over 60% of responding EDs expressed willingness and ability to participate in future research on this topic.